The New Revelation - Doyle, Arthur Conan (Saga Egmont, 2022)
The spiritual movement in the early part of the twentieth century had few proponents greater than Sir Arthur Conan Doyle--a medical doctor, soldier, intellect, and world-renowned author of the Sherlock Holmes series. In 1918, Doyle published The New Revelation--a firsthand account of his personal investigation into the world of Spiritualism, which embraced areas that we refer to today as ESP, New Age philosophy, metaphysics, and psychic experiences. While some may view this work as a historical footnote, the answers to Sir Arthur's basic questions about life and death are as relevant today as they were then.